Analisis Pengaruh Likuiditas dan Profitabilitas terhadap Nilai Perusahaan Menggunakan Pendekatan Regresi Berganda : Studi Kasus pada PT Nippon Indosari Corpindo Tbk Periode 2017–2024 - Asatibi, Ilham Sam Ayub; Apriadi, Deri; Pambudi, Pandu Dwi Luhur (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This study investigates the impact of liquidity and profitability on firm value at PT Nippon Indosari Corpindo Tbk over the 2017–2024 period. Liquidity is measured using the Current Ratio, while profitability is represented by Return on Assets (ROA) and Return on Equity (ROE). Firm value is proxied by the Price to Book Value (PBV). A multiple linear regression model is employed, complemented by univariate and bivariate analyses to mitigate potential multicollinearity between ROA and ROE. The findings reveal that neither the Current Ratio nor ROA significantly affects PBV, with an R-squared value of 0.175 and an F-statistic of 0.5315 (p = 0.618). An alternative model incorporating ROE yields similar results. While the model satisfies the assumptions of residual normality (Jarque-Bera p = 0.654) and shows no indication of significant autocorrelation (Durbin-Watson = 1.458), its explanatory power remains limited. These results suggest that external factors—such as market sentiment and long-term growth expectations—may have a more substantial influence on firm value than internal financial indicators.